2012
DOI: 10.2337/db12-0291
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α Improves Glucose Homeostasis in Skeletal Muscle in an Activity-Dependent Manner

Abstract: Metabolic disorders are a major burden for public health systems globally. Regular exercise improves metabolic health. Pharmacological targeting of exercise mediators might facilitate physical activity or amplify the effects of exercise. The peroxisome proliferator–activated receptor γ coactivator 1α (PGC-1α) largely mediates musculoskeletal adaptations to exercise, including lipid refueling, and thus constitutes such a putative target. Paradoxically, forced expression of PGC-1α in muscle promotes diet-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
75
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 53 publications
(67 reference statements)
6
75
1
1
Order By: Relevance
“…In an extension of these studies, we now, however, found additional genes involved in this process that show an additional, or in the case of Nr0b2, even an exclusive synergistic activation by exercise in the PGC-1␣ transgenic animals. Thus, combined with previous descriptions of muscle plasticity in these mice postexercise in regard to insulin sensitivity (29), our present findings reiterate the importance of bona fide exercise even in a genetic model for endurance training such as the PGC-1␣ musclespecific transgenic animals. In summary, our data provide a first insight into the transcriptional network controlled by PGC-1␣ in muscle cells.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In an extension of these studies, we now, however, found additional genes involved in this process that show an additional, or in the case of Nr0b2, even an exclusive synergistic activation by exercise in the PGC-1␣ transgenic animals. Thus, combined with previous descriptions of muscle plasticity in these mice postexercise in regard to insulin sensitivity (29), our present findings reiterate the importance of bona fide exercise even in a genetic model for endurance training such as the PGC-1␣ musclespecific transgenic animals. In summary, our data provide a first insight into the transcriptional network controlled by PGC-1␣ in muscle cells.…”
Section: Discussionsupporting
confidence: 55%
“…The running protocol is as follows: 10 m/min for 5 min with an increase of 2 m/min every 5 min until 26 m/min and an inclination of 5 degrees. The speed of 26 m/min was kept until exhaustion of the mice (7,28,29). Mice were killed and tissues were collected 3 h after exercise.…”
mentioning
confidence: 99%
“…It has been well established that slow myofi bers are more resistant to damage under stress conditions, such as muscular dystrophy and diabetes (43)(44)(45). In addition, slow myofi bers express high levels of the mitochondrial biogenesis-determinant genes Pgc1 ␣ and PPAR ␦ ; therefore, they are more sensitive to insulin-regulated glucose uptake and may provide beneficial metabolic effects (46)(47)(48)(49). Expression of CD34 or Sca1, two stem-cell markers, is associated with the myogenic potential of progenitor cells derived from bone marrow, blood, and embryonic vasculature (50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…PGC-1␣ is considered a master regulator of mitochondrial biogenesis and function, acting as an upstream regulatory switch for gene pathways controlling oxidative phosphorylation, fatty acid oxidation, reactive oxygen species detoxification, and mitochondrial density. Overexpression of PGC-1␣ in muscle protects aging mice from age-related muscle wasting and glucose intolerance (50,52), and yet tight regulation of PGC-1␣ expression is required to maintain efficient glucose and lipid handling in obese mice (6,19,51). Expression of Pgc-1␣ in muscle is low in type 2 diabetics and related family members (2,21,33,38) but can be increased with exercise to possibly prevent or reverse metabolic abnormalities (3,25,44,49).…”
mentioning
confidence: 99%